1979
DOI: 10.1002/bms.1200060606
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites of loperamide in rats

Abstract: Following intraperitoneal administration to rats of [14C]loperamide, [carbonyl-14] 4-(p-chlorophenyl)-4-hydroxy-N,N-dimethyl-alpha, alpha-diphenyl-1-piperidine butyramide, metabolites in feces and urine were separated, and identified by means of mass spectrometry. In feces, six metabolites were identified in addition to the unchanged drug. The main metabolic pathways involved are dealkylation in the dimethyl amide moiety to give desmethyl- and didesmethylloperamide, both of which were in turn monohydroxylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…An investigation of these problems was therefore made, using [l4C]loperamide labeled at the carbonyl carbon. The extensive metabolism of loperamide observed has been reported in a previous paper (7) while the present paper describes the disposition of [l4C]loperamide in rats and gives additional metabolic data.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…An investigation of these problems was therefore made, using [l4C]loperamide labeled at the carbonyl carbon. The extensive metabolism of loperamide observed has been reported in a previous paper (7) while the present paper describes the disposition of [l4C]loperamide in rats and gives additional metabolic data.…”
Section: Introductionmentioning
confidence: 77%
“…Fecal homogenate and urine were fractionated into basic and acidic fractions by shaking with chloroform at an alkaline and then at an acidic pH and the remainder was considered the polar fraction, as described in a previous paper (7). The polar fraction of urine was adjusted to pH 6.8 with phosphate buffer, and incubated at 3"JOC for 16 hrs with bacterial type-I (3-glucuronidase (Sigma Chemicals Co., Ltd., St. Louis, U.S.A.): the enzyme treatment was confirmed to be sufficient for complete hydrolysis.…”
Section: Ouantitative and Qualitative Analyses Of Fecal And Urinary Mmentioning
confidence: 99%
“…The low efficacy of loperamide in our study could be related to a metabolic reaction due to drug interactions. Loperamide is mainly metabolized to desmethyl loperamide (DLOP) through the N-demethylation pathway [37,38], and clinical studies have shown that DLOP formed by LOP N-demethylation is a major metabolite of LOP in humans [39,40]. Moreover, it has been demonstrated that CYP2B6, CYP2C8, CYP2D6, and CYP3A4 catalyze LOP N-demethylation in human liver microsomes, and among them, CYP2C8 and CYP3A4 may play a crucial role in loperamide N-demethylation at therapeutic concentrations [41].…”
Section: Discussionmentioning
confidence: 99%
“…For example, despite high doses and high plasma concentrations in human subjects, loperamide almost completely lacks central nervous system effects, because P-gp efficiently blocks virtually all uptake by the brain. Loperamide is rapidly metabolized in mammals mainly by dealkylation of the dimethyl amide moiety (12,13). Some metabolites of loperamide, including N-desmethyl-loperamide (N-dLop), are predicted to have adequate lipophilicity to enter the brain if not inhibited by P-gp.…”
mentioning
confidence: 99%